Development of Ectourism In Limboto Lake Through Supply and Demand Approach - Mano, Debby Hariyanti J.; Hasim, Hasim; Hamidun, Marini Susanti (Universitas Negeri Gorontalo, 2023)
Limboto Lake is one of the lakes in Indonesia which is increasingly degraded due to uncontrolled sedimentation rates and aquatic plant populations, causing siltation. This study seeks to identify the ecotourism potential in Limboto Lake with a supply and demand approach. It applied questionnaires distribution, observation, and literature study method, while the analysis used is scoring and descriptive. Based on findings, Limboto Lake possesses supply aspects, including tourist attractions, facilities, accessibility, and community. For tourist attractions, there are a variety of lake activities that can be turned into ecotourism attractions, as well as the biodiversity of flora and fauna, art, and culture. In addition, the tourist facilities are still minim, which requires supporting facilities such as public toilets, homestays, information boards, and parking. Further, demand potential includes the characteristics, motivation, and tourists' desires/demands. The tourists are dominated by women, and domestic tourists, with frequent visits. The main activity for a visit is lake boating, and the most preferred object is the natural scenery. Information about the potential for ecotourism with conservation principles can be one way to support efforts to save Limboto Lake.